2017
DOI: 10.1111/jfpe.12653
|View full text |Cite
|
Sign up to set email alerts
|

Thermal convection coefficient in cooling process of lime fruit: Study through the Galerkin finite element method

Abstract: Cooling is applied to horticultural products to reduce exposition time to inappropriate temperatures. In the present work, a mathematical model was proposed to describe the cooling behavior of lime fruit and to determine the thermal convection coefficient (h) involved. The Galerkin finite element method was used to obtain a numerical solution of the model and results were evaluated by comparing with experimental information. The coefficient h was dependent on fruit position in the cooling system, varied betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…One of them is refrigeration, a rapid decrease in heat after harvesting the fruit. This process involves heat transfer, where a conduction mechanism acts within the product and a convection develops outside the product (Galo et al, 2018; Guadarrama, Perez, Cruz, & Schlam, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…One of them is refrigeration, a rapid decrease in heat after harvesting the fruit. This process involves heat transfer, where a conduction mechanism acts within the product and a convection develops outside the product (Galo et al, 2018; Guadarrama, Perez, Cruz, & Schlam, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Most fresh horticultural products required immediate cooling to retain their freshness and to improve their economic benefit due to their characteristics of high moisture content, high sugar content, and large field heat of the horticultural products (Duan et al, 2020; Han, Ji, Zuo, & Yang, 2021; Mercier, Brecht, & Uysal, 2019; Shen, Zhang, Cao, & Jiang, 2018; Valle‐Guadarrama, Cruz‐Pérez, López‐Cruz, & Hahn‐Schlam, 2018). Forced air pre‐cooling (FAC) was acknowledged as the most common and effective pre‐cooling method due to the advantages of adapting to a variety of horticultural products, rapid cooling, and low cost (Cotrim, Coimbra, & Cotrim, 2021; Redding, Yang, Shim, Olatunji, & East, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…If the air temperature of FAC was lower than the freezing point temperature of the horticultural products, the chilling injury occurred due to the water freezing in in horticultural products to reduce their economic values (Han, Zhao, Qian, Ruiz‐Garcia, & Zhang, 2018; Hussain, Kamal, & Hafiz, 2021). This meant that it was an effective way to accelerate the cooling rate and prolong the shelf life of horticultural products by increasing the air velocity rather than decreasing the air temperature (Valle‐Guadarrama, Cruz‐Pérez, López‐Cruz, & Hahn‐Schlam, 2018; Wang, Fan, Li, & Liu, 2021). For example, it was found that the pre‐cooling time would be decrease 2 ˜ 3 times with the air velocity from 0.2 to 3.6 m s −1 by Lambrinos, Assimaki, and Manolopoulou (1997).…”
Section: Introductionmentioning
confidence: 99%